Alva Noë. Out of our heads: Why you are not your brain, and other lessons from the biology of consciousness - Laura Machado do Nascimento (Principia: An International Journal of Epistemology, 2012)
Review: NOË, Alva. Out of our heads: Why you are not your brain, and other lessons from the biology of consciousness. New York: Hill and Wang, 2009. 214 páginas